Age of Migration and the Incidence of Cognitive Impairment: A Cohort Study of Elder Mexican-Americans. Issue 3 (2nd February 2018) - Garcia, Marc A; Reyes, Adriana M; Downer, Brian; Saenz, Joseph L; Samper-Ternent, Rafael A; Raji, Mukaila
Abstract: Background and Objectives: To explore nativity and age of migration differentials in the incidence of cognitive impairment among older Mexican-Americans. Research Design and Methods: We employ maximum-likelihood discrete time hazard models to estimate risk ratios of cognitive impairment in a sample of 2, 708 Mexican-Americans 65 and older who were cognitively healthy at baseline over a follow-up period of up to 20 years. Results: Late-life immigrant women have a 46% higher risk of cognitive impairment compared to U.S.-born Mexican-American women. Conversely, midlife immigrant men have a 29% lower risk of cognitive impairment compared to U.S.-born Mexican-American men. The incidence of cognitive impairment did not differ for early-life and midlife immigrant women relative to U.S.-born women or for early- and late-life immigrant men compared to U.S.-born men. Discussion and Implications: Differences in cognitive impairment risk between U.S.-born and foreign-born Mexican-American subgroups may be partly due to health selectivity. Cognitive impairment is more prevalent among immigrant groups which may result in a higher burden on family members and/or high dependency on public resources. Programs are needed that can detect decline at earlier stages and reduce the risk for cognitive impairment among older immigrants entering their last decades of life.